Against the Grain: Elite Consensus, Press Independence and the 2006 Israel-Lebanon War. (18th November 2021) - Rowling, Charles M.; Gilmore, Jason; McCue, Patrick
ABSTRACT: This study examines the political and news discourse that surrounded the 2006 Israel-Lebanon War. We use this as a case study to engage the broader scholarly debate over the process and conditions under which U.S. news coverage aligns with, or exhibits independence from, the views expressed by government officials. Specifically, we systematically analyze White House, congressional and U.S. news discourse throughout the war. We find that officials consistently invoked the narrative that the United States should, for both moral and strategic reasons, support Israel. Nonetheless, news coverage in the New York Times and CNN did not reflect the level of consensus that existed among these officials. Instead, journalists exercised considerable independence, routinely identifying and amplifying dissenting opinion, especially from foreign sources, that challenged the dominant narrative expressed by U.S. officials.